Stunting Reduction Policy Targets in The Community: Does Dietary Diversity Matter? - Rina Nur Hidayati; Ahmad Musadek (Nutrition Science and Health Research, 2026)
The prevalence of stunting in children under five remains a global and national public health challenge. Although various policies have been targeted to reduce stunting cases in the community, dietary diversity plays a key role in determining the quality of children's nutritional intake and preventing chronic malnutrition. Information on what dietary diversity is important is needed so that appropriate stunting reduction policy targets can be determined. This study aims to determine the relationship between dietary diversity and the dominant factors associated with the prevalence of stunting. The study design used correlation analysis with a cross-sectional approach. The study population was all children under five and families in stunting locus villages in the UPTD Trawas Health Center area of Mojokerto Regency, totaling 1734 people. Sampling was carried out using proportional cluster sampling with a total of 315 people. Data were obtained through a dietary diversity questionnaire measured by the DDS, and stunting incidence was measured by the Height/Age index (HAZ). Bivariate analysis used chi- square, and multivariate analysis used multiple logistic regression. The results showed a relationship between dietary diversity and stunting (P 0.001, OR 6.532, CI 3.158- 13.510). There was an association between consumption of vitamin A-rich fruits and vegetables (P 0.037, OR 4.221), meat and fish consumption (P 0.002, OR 5.101), egg consumption (P 0.039, OR 4.145), and milk consumption (P 0.048, OR 1.938) and stunting in children under five. Meat and fish consumption were the dominant variables influencing stunting (P 0.020, AOR 4.205). This study recommends that policymakers, particularly the Ministry of Health, prioritize dietary diversity in efforts to reduce stunting, with a primary focus on ensuring adequate animal protein intake.